#TITLE_ALTERNATIVE# - MANDA PATRIA (NIM : 22710005); Dr. Ir. Lilik Eko Widodo, MS, ANDINI
East Ertsberg Skarn System (EESS) is a mining complex at PT.Freeport Indonesia (PTFI) with one of the existing mine area i.e. the Deep Ore Zone EESS (DOZ). It has been mined using block-caving, by which wet muck is one of the potentially risk that may affect mining production. The increase of groundwater and fine material have resulted in wet muck and can lead to mud rush. It is an important aspect that must be considered to determine the water balance in mining and related safety. Groundwater flow in EESS area is controlled by geological structure that is dominated by fractures. They can store water and may build aquifers. Groundwater flow in fractured media in this study can be distinguuished from the flow in porous media that is previously applied by PT Freeport. The hydraulic conductivity (K) of each lithology in the EESS has been determined using the HC-system that will be used to numerically simulate the groundwater flow by using finite element method (FEM), which in turn can be exucuted using FEFlow modelling software. Simulation results from groundwater flow show that the flow direction is toward the cave, to west fault zone (WFZ) and as well as to east fault zone (EFZ). The inflow into the model area was estimated around 15640 gpm and the groundwater is drained due to dewatering to be around 13400 gpm with water content 3148 gpm in fine material.